2012
DOI: 10.1016/j.schres.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic specificity of poor premorbid adjustment: Comparison of schizophrenia, schizoaffective disorder, and mood disorder with psychotic features

Abstract: Individuals with schizophrenia have significant deficits in premorbid social and academic adjustment compared to individuals with non-psychotic diagnoses. However, it is unclear how severity and developmental trajectory of premorbid maladjustment compare across psychotic disorders. This study examined the association between premorbid functioning (in childhood, early adolescence, and late adolescence) and psychotic disorder diagnosis in a first-episode sample of 105 individuals: schizophrenia (n=68), schizoaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Future studies should consider the combination of subjective and objective measures to capture a more comprehensive picture of the patient outcomes . Moreover, the study of other characteristics that may be influencing functional outcomes such as premorbid social and academic adjustment , contextual factors and personality traits , social cognition and proxies of cognitive reserve would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should consider the combination of subjective and objective measures to capture a more comprehensive picture of the patient outcomes . Moreover, the study of other characteristics that may be influencing functional outcomes such as premorbid social and academic adjustment , contextual factors and personality traits , social cognition and proxies of cognitive reserve would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…an individual’s functioning across social and academic domains from childhood through to early adulthood prior to the onset of psychosis) has long been a focus of interest in schizophrenia research [2]. Deficits in premorbid adjustment are reported consistently as a precursor to schizophrenia [3], and as such provide supportive evidence for the neurodevelopmental model [45]. For example, poor social adjustment during childhood has been proposed as an early manifestation of impairment of developmental trajectories that evolve into deficits in social cognition and later into schizophrenia [6].…”
Section: Introductionmentioning
confidence: 99%
“…While some have suggested that social functioning is similarly poor between individuals with non-affective or with affective psychosis (e.g., Bellack et al, 1989; Simonsen et al, 2010), others have reported that those with affective psychosis have significantly better social functioning (e.g., Tarbox et al, 2012). Given that older ages are associated with greater social dysfunction in both SZ (Gould et al, 2012; Mueser et al, 2010) and bipolar disorder with and without psychotic features (Depp et al, 2007; Mueser et al, 2010), one possible reason for discrepant findings is differing age ranges of participants across investigations.…”
Section: Introductionmentioning
confidence: 99%